Morphological Marking Irregularity of Bahasa Indonesia and the Acquisition of English Words - Bambang Agus Darwanto; Pratomo Widodo; Hesthi Heru Satoto (Soegijapranata Catholic University, 2020)
Abstract: All languages share the same lexical categories such as verb, noun, adjective, and adverb. Unlike English, however, Bahasa Indonesia carries fewer consistent patterns of morphological markers for word categories. A verb, for instance, is marked with the prefix me- as in me-nginjak (to step on); however, other verbs do not carry this marker as in makan (eat), tidur (sleep), and tergantung (depend). As for English, the suffix -ing or -ed/-en, for instance, indicates that the root is a verb regardless of the verb transitivity. This research investigated if the irregularity in the morphological marking of Bahasa Indonesia verbs created problems in acquiring English words. A test of the